Community Views and Public Health Priority Setting: How Do Health Department Priorities, Community Views, and Health Indicator Data Compare?. Issue 1 (January 2015) - Earle-Richardson, Giulia; Scribani, Melissa; Wyckoff, Lynae; Strogatz, David; May, John; Jenkins, Paul
Objectives. New York, like many other states, provides county-level health statistics for use in local priority settings but does not provide any data on public views about priority health issues. This study assessed whether health department priorities are notably different from community concerns about health, and how both groups' priorities compare with local health statistics. Method. Data from a 2009 rural survey on community health concerns were compared to priorities named by the seven area county health departments, and to local health indicator data. Results. Health care/insurance cost (60%), obesity (53%), and prescription cost (41%) were leading community concerns, regardless of age, education, sex, or Internet in the home. Six of seven county health departments selected access to quality health care (which includes health care/insurance cost) as a leading public health priority, but only three identified obesity. The following leading local health issues were suggested by health indicators: Physical activity and nutrition, Smoking, and Unintentional injury. Conclusions. Health departments diverged from community priorities, from health indicator data, and from one another in choosing priorities. Adding a question about community health priorities to existing state telephone surveys on health behavior and lifestyle would provide an important tool to local health departments.